Pengaruh Kinerja Pelayanan Pegawai Bagian Administrasi Umum terhadap Tingkat Kepuasan Sivitas Akademika di Politeknik Harapan Bersama Kota Tegal - Bahri Kamal; Muhamad Bakhar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to find out the effects of the service performance of the general administration staff on the level satisfaction of the academic community at the harapan bersama polythechnic tegal. The sample was selected by means of the slovin formula technique and it consisted of 98 consumers. The techniques used in data collection were observation, interview, literature, and questionnaire. The data analysis techniques were quantitative with the statistic analysis descriptive quantitative, data quality test (validity test and reliability test), classic assumption test (normality’s test, multicolonierity test, heteroskedasticity test, and autocorrelation test), multiple linear regression, hypotesis’s test (t’s test and F’s test) and coefficient of determination. The results of the research show that : (1) there is a positive and significant partially between effect of the service performance in cleanliness on the satisfaction of the academic community at the Harapan Bersama Polythechnic Tegal, indicated by a regression coefficient of 0,286, a tobserved value of 4,472, and a significance value of 0,000; (2) there is a positive and significant partially between effect of the service performance in infrastructure on the satisfaction of the academic community at the Harapan Bersama Polythechnic Tegal.